Proteomic and biological profiling of extracellular vesicles from Alzheimer's disease human brain tissues. Issue 6 (17th April 2020) - Muraoka, Satoshi; DeLeo, Annina M.; Sethi, Manveen K.; Yukawa‐Takamatsu, Kayo; Yang, Zijian; Ko, Jina; Hogan, John D.; Ruan, Zhi; You, Yang; Wang, Yuzhi; Medalla, Maria; Ikezu, Seiko; et al.
Abstract: Introduction: Extracellular vesicles (EVs) from human Alzheimer's disease (AD) biospecimens contain amyloid beta (Aβ) peptide and tau. While AD EVs are known to affect brain disease pathobiology, their biochemical and molecular characterizations remain ill defined. Methods: EVs were isolated from the cortical gray matter of 20 AD and 18 control brains. Tau and Aβ levels were measured by immunoassay. Differentially expressed EV proteins were assessed by quantitative proteomics and machine learning. Results: Levels of pS396 tau and Aβ1–42 were significantly elevated in AD EVs. High levels of neuron‐ and glia‐specific factors are detected in control and AD EVs, respectively. Machine learning identified ANXA5, VGF, GPM6A, and ACTZ in AD EV compared to controls. They distinguished AD EVs from controls in the test sets with 88% accuracy. Discussion: In addition to Aβ and tau, ANXA5, VGF, GPM6A, and ACTZ are new signature proteins in AD EVs.